2001
DOI: 10.4049/jimmunol.167.8.4616
|View full text |Cite
|
Sign up to set email alerts
|

Intracisternally Localized Bacterial DNA Containing CpG Motifs Induces Meningitis

Abstract: Unmethylated CpG motifs are frequently found in bacterial DNA, and have recently been shown to exert immunostimulatory effects on leukocytes. Since bacterial infections in the CNS will lead to local release of prokaryotic DNA, we wanted to investigate whether such an event might trigger meningitis. To that end, we have intracisternally injected mice and rats with bacterial DNA and oligonucleotides containing CpG motifs. Histopathological signs of meningitis were evident within 12 h and lasted for at least 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 65 publications
5
58
1
1
Order By: Relevance
“…We therefore hypothesized that CpG-DNA would aggravate a preexisting immune complex GN, a hypothesis confirmed by our results. The worsening of glomerular damage was associated with marked macrophage infiltration, a finding also noted by others using CpG-ODN in various disease models (23)(24)(25). Further analysis revealed, as a novel mechanism, that CpG-DNA-TLR9 interaction induced chemokine and chemokine receptor expression in macrophages.…”
supporting
confidence: 70%
“…We therefore hypothesized that CpG-DNA would aggravate a preexisting immune complex GN, a hypothesis confirmed by our results. The worsening of glomerular damage was associated with marked macrophage infiltration, a finding also noted by others using CpG-ODN in various disease models (23)(24)(25). Further analysis revealed, as a novel mechanism, that CpG-DNA-TLR9 interaction induced chemokine and chemokine receptor expression in macrophages.…”
supporting
confidence: 70%
“…TLR activation may therefore play a major role during septic shock, systemic inflammatory response syndromes, and local immune responses (8,(82)(83)(84)(85)(86)(87)(88)(89)(90). In macrophages, the expression of CCchemokines and CC-chemokine receptors by TLR9 activation may contribute to additional leukocyte infiltration to the site of injury as it has been observed in several disease models, including GN (87)(88)(89)(90).…”
Section: Biologic Effects Induced By Tlr Activation On Immune Cellsmentioning
confidence: 99%
“…Furthermore, animal studies have indicated that the cell wall from different strains of B. adolescentis caused different pro-inflammatory responses because of the differences in the component of peptidoglycan (22). Besides differences in cell wall components, unmethylated CpG motifs frequently found in bacterial DNA have recently been shown to exert immunostimulatory effects on leukocytes through interaction with the toll-like receptor on the surfaces of leukocytes (4). These motifs are present in varying amounts in different bacterial species and strains and may be another explanation for the observed differences in immune stimulation by the tested bifidobacteria.…”
mentioning
confidence: 99%